2011
DOI: 10.1590/s0034-89102011005000005
|View full text |Cite
|
Sign up to set email alerts
|

Permanent vascular access in patients with end-stage renal disease, Brazil

Abstract: METHODS:Cross-sectional study conducted in a nationally representative sample of Brazilian end-stage renal disease patients in dialysis and transplant centers during 2007. The sample comprised only patients who received hemodialysis as a primary therapy modality and reported the type of vascular access for their primary hemodialysis treatment (N=2,276). Data were from the TRS Project -"Economic and Epidemiologic Evaluation of Modalities of Renal Replacement Therapy in Brazil". Multiple logistic regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…4 Despite being a safe option in emergency situations, unlike the permanent vascular access, temporary venous catheters have a high incidence of complications, such as infection, thrombosis, lower dwell time compared to other vascular accesses, and a lower blood flow rate, which reduces the effectiveness of hemodiaysis. [5][6] The temporary catheter is primarily responsible for about 48-73% of bacteremia occurring in patients on hemodialysis treament. 7 The high incidence of intravenous line-related infections has stimulated the development of studies to determine the specific elements that cause this phenomenon because general factors such as clinical conditions, extremes of age and comorbidities such as diabetes, hypertension, obesity and malnutrition are already known.…”
Section: Introductionmentioning
confidence: 99%
“…4 Despite being a safe option in emergency situations, unlike the permanent vascular access, temporary venous catheters have a high incidence of complications, such as infection, thrombosis, lower dwell time compared to other vascular accesses, and a lower blood flow rate, which reduces the effectiveness of hemodiaysis. [5][6] The temporary catheter is primarily responsible for about 48-73% of bacteremia occurring in patients on hemodialysis treament. 7 The high incidence of intravenous line-related infections has stimulated the development of studies to determine the specific elements that cause this phenomenon because general factors such as clinical conditions, extremes of age and comorbidities such as diabetes, hypertension, obesity and malnutrition are already known.…”
Section: Introductionmentioning
confidence: 99%
“…A Brazilian cross-sectional study comprising 2,276 patients reported a prevalence of 69% for NTCs at HD initiation. The risk factors for NTC use include pre-dialysis care for less than 1 year and lack of private insurance ( 11 ). A retrospective analysis of 5,081 Brazilian patients, 58.1% of whom were covered by the public health insurance system, found that, for 69.6% of patients, dialysis was initiated with a catheter (56% NTC and 13.6% TC) ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sesso et al (2008) 10 found that 34% of patients who started hemodialysis used fistulas. The other 66% were referred to the nephrologist to immediately start hemodialysis through a catheter 51 . The findings in Ceará were lower than the national ones for 2008 and there are not such comprehensive data for comparison.…”
Section: Discussionmentioning
confidence: 99%